Modal Sosial dalam Pengembangan Usaha : (Studi pada Perusahaan Multilevel Marketing, Tiens Group di Kota Banda Aceh) - Khairulyadi, Khairulyadi; Bukhari, Bukhari; Nazria Arrahyu (Yayasan Literasi Sains Indonesia, 2024)
As a foreign company, Tiens Group has been successful and well accepted by the people of Banda Aceh, a city known for the implementation of Syariah Islam. This study analysed how the company uses its social capital resulting in its acceptance by the host society that is strongly associated with Syariah Islam. This research uses sosial capital theory by Robert D. Putnam. It is a qualitative reseach. Data were collected through interview and participant observation. This research found that the company has utilized sosial capital and succeeded in achieving its targets and well accepted by the host society. The interplay of the three aspects of sosial capital namely norms, trust and networks have been influential in achieving success of the company. Norms has been a focal point in the formation of group identity. It is the values that give rise to a strong trust among its members. Trust is formed through a strong believe towards values and norms. Network is needed to bridge and help expand the company to people outside the company through new recruits (bridging sosial capital), while at the same time, network within the group, would eventually strengthen the norms and the trust system as well as the sense of solidarity and work ethics among the members (bonding sociap capital).